FOLK HERBAL VETERINARY MEDICINES FROM INDIAN DESERT - Katewa, S. S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Traditional medicines, especially the folk herbal medicines have recently been receiving heightened interest the world over. The World Health Organization (WHO) in its document on “Health for all by the year 2000” has accepted the role traditional medicine has to play in primary health care [1]. The animals are needed for the well being of the humans and hence the similar application of traditional medicine is now being advocated by food and Agricultural Organization (FAO) for animal treatment [2, 3, 4, 5], as is being done by WHO for human treatment. Indian desert is endowed with xerophytic vegetation and the native people have learnt to utilize these plants to meet the health care needs for millennia. The knowledge is believed to be collectively owned by ancestors and kept under the custody of living old men and women, depending on the community, ethnic, sex, age, caste etc. There is a danger however this method of vesting knowledge in human custodians can be undermined by mortality, thereby losing important information to the future generations. Considering the therapeutic potentials of herbal drugs to be of help in animal treatment and production, the author carried out the Ethnoveterinary survey of Indian Desert on the contribution of such a dynamic folk system of herbal medicine practiced by the hereditary physician belonging to certain ethnic communities. In the present communication, therapeutic uses of 25 plant species against animal diseases mentioning their Botanical identity, family, mode of administration and dosage have been given. This folk wisdom if subjected to scientific scrutiny could benefit the humankind in many ways